2008
DOI: 10.1007/s10592-008-9582-5
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity and recovery implications of the vulnerable Bankoualé Palm Livistona carinensis (Arecaceae), from North-eastern Africa and the Southern Arabian Peninsula

Abstract: The Bankoualé Palm, Livistona carinensis is the only known species of Livistona occurring in Africa and is currently classified as vulnerable (IUCN 2004). This extreme outlier species of the genus is restricted to Yemen, Somalia and Djibouti, where all populations are in rapid decline. In Djibouti the palm is confined to three valley systems within the upland plateau of the Goda Massif. This study used microsatellite markers to investigate the genetic diversity and relationships within the species. At the spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 62 publications
1
11
1
Order By: Relevance
“…An extremely low value of polymorphism (6.17%) was reported for Livistona carinensis, an endangered palm species (Shapcott et al, 2009). However, given the wide geographic distribution of the palm species investigated in our study, we would have expected higher levels of polymorphism.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…An extremely low value of polymorphism (6.17%) was reported for Livistona carinensis, an endangered palm species (Shapcott et al, 2009). However, given the wide geographic distribution of the palm species investigated in our study, we would have expected higher levels of polymorphism.…”
Section: Discussioncontrasting
confidence: 54%
“…Other population genetic structure parameters, such as Wright's inbreeding coefficient and gene flow, have shown that, in general, genetic differentiation (F ST ) is low, indicating genetic variation higher within -rather than among -populations and a high gene flow among populations (Elshibli and Korpelainen, 2008;Martins-Corder et al, 2009;Shapcott et al, 2009;Namoff et al, 2011;Silva et al, 2011;Giovino et al, 2014;Nazareno and dos Reis, 2014;Oliveira et al, 2014;Moura et al, 2015). Recently, Ramos et al (2016) found a high level of genetic diversity, mostly within populations, for adults and seedlings in populations of A. aculeatum, and along with results for spatial genetic structure indicated short-distance seed dispersal and modest levels of pollen flow.…”
Section: Introductionmentioning
confidence: 99%
“…Low genetic variation is expected for isolated endemic species with small population size (Young and Clarke 2000;Leimu et al 2006). The level of genetic diversity within L. mooreana was moderate compared with other endemic or rare palm species (Dowe et al 1997;Shapcott 1998;González-Pérez et al 2004;Henderson et al 2006;Shapcott et al 2007Shapcott et al , 2009, other more widespread species present on LHI (Savolainen et al 2006;Babik et al 2009) and widespread palm species elsewhere (e.g., Eguiarté et al 1992;Luna et al 2007), indicating some potential for genetic resilience.…”
Section: Plastic Responses To Climate Changementioning
confidence: 98%
“…Therefore, the conservation, regeneration, distribution, and utilization of date palm genetic resources will be more urgent in the foreseeable future (Eljuhani 2010 ;Ezebilo et al 2013 ). Date palm wild and feral genotypes that are geographically and ecologically widespread can be assumed to be under less threat of genetic erosion than those localized or restricted to a specifi c habitat; the latter should be given priority in conservation (Francisco-Ortega et al 2000 ;Gaitto et al 2003 ;Shapcott et al 2009 ).…”
Section: The Future Of the Date Palmmentioning
confidence: 99%